Don't Tell Me to Change: A Right to Not Have Transformative Experiences - Silver, Kenneth (Res Philosophica, 2026)
I argue that, given the choice, we have a right not to undergo transformative experiences. We are entitled to affirm our previous autonomous agency by deciding in this way, and this right is grounded in the significance of our self-authorship. I further show that many of the suggested demands of morality involve transformative change, and so meeting these demands would involve not just paying a high cost, but forfeiting this right. Though this may be morally required, we may wrong ourselves in complying.
PUBLISHED
Keywords: Identities in Transformation; Human Rights; Philosophy; Transformative Experience